2023
DOI: 10.1002/advs.202207418
|View full text |Cite
|
Sign up to set email alerts
|

Oral Delivery of Bioactive Glass‐Loaded Core–Shell Hydrogel Microspheres for Effective Treatment of Inflammatory Bowel Disease

Abstract: Resolving inflammation and promoting intestinal tissue regeneration are critical for inflammatory bowel disease (IBD) treatment. Bioactive glass (BG) is a clinically approved bone graft material and has been shown to modulate inflammatory response, but it is unknown whether BG can be applied to treat IBD. Here, it is reported that BG attenuates pro-inflammatory response of lipopolysaccharide (LPS)-stimulated macrophages and hence reduces inflammatory damage to intestinal organoids in vitro. In addition, zein/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 67 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…Macrophages are the primary effector cells of intestinal mucosal immunity, capable of sensing intestinal antigens and participating in intestinal immune responses [ 21 , 22 ]. Previous studies have indicated that longan polysaccharides can reach the intestine in an undigested form without significant changes in immunomodulatory activity [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are the primary effector cells of intestinal mucosal immunity, capable of sensing intestinal antigens and participating in intestinal immune responses [ 21 , 22 ]. Previous studies have indicated that longan polysaccharides can reach the intestine in an undigested form without significant changes in immunomodulatory activity [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al bluepresent a glucose-responsive nanocarrier system for insulin delivery, encapsulated within a three-dimensional hyaluronic acid hydrogel, demonstrating enhanced oral bioavailability and prolonged hypoglycemic effects in diabetic rats compared to insulin-loaded nanocarriers alone [134]. Zhu et al reported the development of bluezein/sodium alginate-based core-shell microspheres (Zein/SA/BG) for oral delivery of bioactive glass (BG), which helps prevent premature dissolution of BG in the stomach and significantly reduces intestinal inflammation, promotes epithelial tissue regeneration, and partially restores microbiota homeostasis [135]. Miller et al presented a self-assembling, pH-responsive nanoparticle systemblue, which were synthesized via nanoprecipitation using pH-responsive copolymers based on poly(methacrylic acid-co-methyl methacrylate)-block-poly(ethylene glycol), offering a promising non-invasive alternative to injections [136].…”
Section: Oral Hydrogel-based Drug Deliverymentioning
confidence: 99%
“…Alginate is a natural polysaccharide primarily extracted from brown algae. It can serve as a carrier in drug delivery systems to control drug release rates [ 64 ]or be fabricated into various scaffold shapes for tissue engineering applications, mimicking specific tissue structures and providing a platform for cell attachment and growth [ 65 ]. Alginate gels are commonly used as bioink in bioprinting technology to precisely print scaffolds, enabling the construction of specific tissue structures.…”
Section: Strategies For Regenerative Endodonticsmentioning
confidence: 99%